Complement regulatory proteins in kidneys of patients with anti‐neutrophil cytoplasmic antibody (ANCA)‐associated vasculitis. (20th October 2017) - Cheng, L.; Gou, S.‐J.; Qiu, H.‐Y.; Ma, L.; Fu, P.
Summary: The complement system activation is involved in the development of anti‐neutrophil cytoplasmic antibody‐associated vasculitis (AAV). The study aimed to investigate the expression of complement regulatory proteins (CRPs) CD46, CD55 and CD59 in kidneys of 51 AVV patients. The expression of CD46, CD55 and CD59 in kidneys was detected by immunohistochemistry and double immunofluorescence staining. The immunohistochemical examination revealed that expression of the three CRPs could be detected in the glomeruli and tubules of both AAV patients and normal controls. The expression levels of the three CRPs in glomeruli of patients with AAV were significantly lower than those of normal controls. The scores of CD46 and CD55 expression in the tubules of AAV patients were significantly lower than those of normal controls, while there was no significant difference between the scores of CD59 expression in tubules of AAV patients and those of normal controls. Among AAV patients, the expression level of CD46 in glomeruli correlated inversely with the proportion of normal glomeruli, while it correlated with tubular atrophy in renal interstitium ( r  = –0·305, P  = 0·026; r  = 0·330, P  = 0·023, respectively). The expression levels of CD55 and CD59 in glomeruli correlated with the proportion of total crescents ( r  = 0·384, P  = 0·006; r  = 0·351, P  = 0·011, respectively). Double immunofluorescence staining indicated that all three CRPs were expressed on endothelial cells, podocytes and mesangial cells in glomeruli. The expression levels of the three CRPs were dysregulated in kidneys of patients with AAV. The expression levels of CD46, CD55 and CD59 were associated with the severity of renal injury of AAV patients. Abstract : This paper first showed the expression levels of mCRPs were down‐regulated in kidneys of patients with AAV and the expression levels of mCRPs were associated with the severity of renal injury of AAV patients.